Towards money market in general equilibrium framework - Truong Hong Trinh (International Journal of Financial Studies, 2022)
This paper aims to integrate the money market into the structure of the economy. The microfoundation is the starting point to define the money market and the general equilibrium mechanism of the economy. On this basis, this research seeks a linking mechanism of the money market with economic activity in the general equilibrium framework. The relationships between money supply and national outcome, inflation, and price level are studied in three cases: full-employment equilibrium economy, steady-state equilibrium economy, and sticky-price equilibrium economy. The research result explains the interrelation and transmission mechanism between the money market and the general equilibrium of the economy. The paper provides the theoretical foundation for further research on the money market and monetary policies towards economic growth and macroeconomic stability.
Keywords: D01; D50; E40; E52; 330; economic growth; general equilibrium; inflation; microfoundations; money market